Comparison of Alvarado scores, Tzanakis scores, and RIPASA scores in the diagnosis of acute appendicitis in Sanglah Hospital - I Made Maha Satya Dwi Palguna; Made Agus Dwianthara Sueta; Tjokorda Gde Bagus Mahadewa (Indoscholar, 2022)
Background: Acute appendicitis (AA) is the most common cause of gastrointestinal emergency surgery worldwide. However, to confirm the diagnosis of acute appendicitis, it is largely dependent on clinical judgment, causing the rate of negative appendectomy or misdiagnosis reach 20 – 40%. Several scoring systems have been developed to identify patients who did not require surgery, thereby reducing the burden of negative appendectomy. Methods This study is a cross-sectional observational study with diagnostic tests. The study was conducted at the Surgical Department of Sanglah Hospital, Denpasar from January 1st, 2020 to December 31st, 2020. All patients enrolled in this study were calculated with Alvarado, Tzanakis, and RIPASA scores to determine the need for appendectomy. In patients undergoing surgery, the diagnosis of AA was confirmed by histopathological examination. Descriptive analysis, receiver operating characteristics (ROC) analysis, and diagnostic tests were used to assess the effectiveness of the three scoring systems. Results: The total respondents in this study who met the inclusion and exclusion criteria were 103 people. This study found that acute appendicitis was more common in male patients with a mean age of 28.26 years. The RIPASA scoring system has better sensitivity and accuracy than the Alvarado and Tzanakis scores, so it is recommended to use the RIPASA score as a diagnosis of acute appendicitis. However, if an ultrasound facility is available, the Tzanakis score can be used. Conclusion: RIPASA score is the best score to diagnose acute appendicitis.